Avaliação das indicações de ceratoplastia penetrante no interior paulista - Barbosa, Amanda Pires; de Almeida Junior, Gildasio Castello; Teixeira, Marta Ferrari; Barbosa, Jose Carlos [UNESP] (Soc Brasileira Oftalmologia, 2012)
Objective: To determinate the corneal diagnoses of patients underwent Penetrating Keratoplasty (PK) in the university hospital of Sao Jose do Rio Preto, São Paulo, Brazil, and their relation to age group, gender and socioeconomic factors. Methods: Retrospective analysis of 1085 registration forms of patients underwent Penetrating Keratoplasty in the university hospital of Sao Jose do Rio Preto, São Paulo, Brazil, from 2000 to 2009. The surgical indications were then correlated to age group, gender and socioeconomic factors, by chi-square test. Results: Fifty-seven percent of all Penetrating Keratoplasties were performed in male patients, and the mean age was 52.3 years. Most surgeries (90.8%) occurred by means of public health care (SUS). The main diagnosis was leukoma (23%), representing 14% of the indications for PK in males and 9% in females. Leukoma was also the diagnosis in 40% of PK performed in patients older than 60 years and in 94.4% of these surgeries in public health care users. Conclusion: The main indication for Penetrating Keratoplasty was leukoma, predominating in males, ages above 60 years and in public health care users.
Evaluation of penetrating keratoplasty indications in inner part of the São Paulo state
Keywords: Corneal transplantation; Keratoplasty, penetrating; Corneal diseases; Corneal opacity; Retrospective studies